Regulation of Chemokine CCL5 Synthesis in Human Peritoneal Fibroblasts: A Key Role of IFN-γ - Kawka, Edyta; Witowski, Janusz; Fouqet, Nina; Tayama, Hironori; Bender, Thorsten O.; Catar, Rusan; Dragun, Duska; Jörres, Achim (Mediators of Inflammation, 2014)
Peritonitis is characterized by a coordinated influx of various leukocyte subpopulations. The pattern of leukocyte recruitment is controlled by chemokines secreted primarily by peritoneal mesothelial cells and macrophages. We have previously demonstrated that some chemokines may be also produced by human peritoneal fibroblasts (HPFB). Aim of our study was to assess the potential of HPFB in culture to release CCL5, a potent chemoattractant for mononuclear leukocytes. Quiescent HPFB released constitutively no or trace amounts of CCL5. Stimulation of HPFB with IL-1β and TNF-α resulted in a time- (up to 96 h) and dose-dependent increase in CCL5 expression and release. IFN-γ alone did not induce CCL5 secretion over a wide range of concentrations (0.01–100 U/mL). However, it synergistically amplified the effects of TNF-α and IL-1β through upregulation of CCL5 mRNA. Moreover, pretreatment of cells with IFN-γ upregulated CD40 receptor, which enabled HPFB to respond to a recombinant ligand of CD40 (CD40L). Exposure of IFN-γ-treated HPFB, but not of control cells, to CD40L resulted in a dose-dependent induction of CCL5. These data demonstrate that HPFB synthesise CCL5 in response to inflammatory mediators present in the inflamed peritoneal cavity. HPFB-derived CCL5 may thus contribute to the intraperitoneal recruitment of mononuclear leukocytes during peritonitis.